Syntheses of Ketamine and Related Analogues: A Mini Review - Dimitrov, Ivaylo; Denny, William A.; Jose, Jiney (Synthesis, 2018)
Ketamine [2-(2-chlorophenyl)-2-(methylamino)cyclohexanone] is a dissociative anaesthetic, first developed in 1963 by Parke-Davis. It finds widespread application in the treatment of battlefield injuries, and in emergency departments for use in children. In recent times the clinical interest in ketamine has increased due to the positive impact it has in treating depression and the rapid onset of its antidepressant effect. This review covers the synthetic effort towards ketamine and related analogues over the past 60 years to give readers an overview of past, current, and future research outlook pertaining to ketamine-like molecules.1 Introduction2 Early Work3 Synthesis3.1 Ketamine3.2 Norketamine3.3 Ketamine Analogues4 Future Outlook and Conclusion
Keywords: ketamine; anaesthetic; analgesic; antidepressant; norketamine